Cultivating Corpses: A Comparative Approach to Disembodied Mortuary Remains - Anders Kaliff; Terje Oestigaard (Current Swedish Archaeology, 2004)
Disembodied remains of corpses are often found in the archaeological record but seldom interpreted and understood. This mortuary practice challenges our traditional understanding of funerals and what constitutcs a "grave". Through a comparative analysis of prehistoric Bronze Age and Iron Age mortuary remai ns and contemporary funeral practices in Nepal, it is argued that the disembodiment is a cosmogonic act whereby the corpse is an intrinsic part of the agricultural and hydrological cycle. An explicit combination of the past and present for interpretations of the past is a premise for understanding and knowledge production in archaeology, and this theoretical stance is developed and explored.